Association between Dietary Antioxidant Quality Score and Anthropometric Measurements in Children and Adolescents: The Weight Disorders Survey of the CASPIAN-IV Study. (26th August 2020) - Azizi-Soleiman, Fatemeh; Khoshhali, Mehri; Heidari-Beni, Motahar; Qorbani, Mostafa; Kelishadi, Roya
Abstract: Background: Limited experience exists on the relationship between anthropometric measures and dietary antioxidant intake in the pediatric age group. We aimed to investigate the association of dietary antioxidants intake and anthropometric measurement in children and adolescents. Methods: This nationwide study was conducted in 4270 children and adolescents, aged 6–18 years. Demographic and anthropometric data were assessed. Children and adolescents were classified as underweight, healthy weight or overweight/obese based on body mass index percentiles. Dietary intake was obtained by a 168-item semi-quantitative validated food frequency questionnaire. Energy and nutrients intake was estimated using the Nutritionist IV software. Dietary antioxidant quality score (DAQS) was calculated based on the daily dietary intake of selenium, zinc, vitamin A, vitamin C and vitamin E compared with daily recommended intake. Results: After adjustment for age, gender, living area (rural or urban), energy intake and physical activity level, DAQS was positively associated with waist circumference (WC), hip circumference and waist-to-height ratio (WHtR) in under-weight children and adolescents ( B  = 1.614, 1.634 and 0.01, respectively; all p s < 0.05). Increased DAQS was significantly associated with higher WC and WHtR in normal–weight children and adolescents ( B  = 0.536 and 0.003, respectively; all p s <0.05). Conclusion: Dietary intakes of some antioxidants were higher in children and adolescents with excess weight. DAQS was correlated with some anthropometric measurements in under-weight and normal-weight subjects. It can provide a novel approach to assess the role of antioxidant intake on health promotion and diet-based therapies in under-weight and normal-weight children and adolescents